2013
DOI: 10.1109/tvcg.2013.183
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Average Value in Multiclass Scatterplots

Abstract: The visual system can make highly efficient aggregate judgements about a set of objects, with speed roughly independent of the number of objects considered. While there is a rich literature on these mechanisms and their ramifications for visual summarization tasks, this prior work rarely considers more complex tasks requiring multiple judgements over long periods of time, and has not considered certain critical aggregation types, such as the localization of the mean value of a set of points. In this paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 63 publications
(78 reference statements)
2
89
2
Order By: Relevance
“…A follow-up study [17] indicated that a 2D scatterplot is as good as an interactive 3D scatterplot or a scatterplot matrix in showing classes. Gleigher et al [18] explored the visual design of multiclass scatterplots for the task of identifying the mean value of a set of points. Lewis et al [19] compared grouping quality metrics with human evaluations by using a diverse set of measures based on a theoretical taxonomy.…”
Section: Empirical Studies Of Scatterplot Perceptionmentioning
confidence: 99%
“…A follow-up study [17] indicated that a 2D scatterplot is as good as an interactive 3D scatterplot or a scatterplot matrix in showing classes. Gleigher et al [18] explored the visual design of multiclass scatterplots for the task of identifying the mean value of a set of points. Lewis et al [19] compared grouping quality metrics with human evaluations by using a diverse set of measures based on a theoretical taxonomy.…”
Section: Empirical Studies Of Scatterplot Perceptionmentioning
confidence: 99%
“…Recently, it could also be shown that crowdsourcing can be an effective way of investigating the perceptual capabilities of visualizations [Heer and Bostock 2010], which led to the conduction of several interesting crowdsourcing studies in visualization. Prominent examples include the perception of averages in multi-class scatter plots [Gleicher et al 2013], but also the memorability of visualizations [Borkin et al 2013]. However, in the area of scientific visualization not many such studies have been published.…”
Section: Related Workmentioning
confidence: 99%
“…In visualization research, these types of studies can be used to address perceptual and comprehensibility questions [20], whereby low-level tasks such as compare, contrast, associate, distinguish, rank, cluster, correlate or categorize can be considered [40]. Unfortunately, the number of quantitative user evaluations is still rather low [23], despite the fact that these evaluations can be used to address a broad variety of research questions, reaching from aesthetics [41], over spatial comprehension [18], and visual averaging [17] to memorability [3]. Crowdsourcing.…”
Section: Related Workmentioning
confidence: 99%
“…An additional benefit is that participants of crowdsourced user studies can participate at any given time, and is not limited to the opening hours of the lab. While there has not yet been any work published where crowdsourcing has been utilized for evaluating scientific visualization research, crowdsourcing has been successfully utilized for user studies in information visualization [9,10,16,17,19,24,38,47].…”
Section: Introductionmentioning
confidence: 99%